MODEL KOLABORASI DALAM PENGEMBANGAN PARIWISATA BERKELANJUTAN DI DESA SELUMBUNG KECAMATAN MANGGIS KARANGASEM - Ni Luh Putu Ening Permini; I Kadek Dede Junaedy; Ni Kadek Ayu Dewi Purnamasari (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2024)
In each collaboration model, the actors rarely act alone because each collaboration actor has different interests and goals. In addition, an important strategy to realize the right collaboration model in sustainable tourism development is to utilize the characteristics and distinctive features that are owned to meet the needs of tourism development as a whole. The benchmark for assessing the collaboration model is based on how big the relationship between the collaboration actors is, both directly and indirectly, including: business cooperation, communication, knowledge, trust, mutual understanding, dialogue, benefits of cooperation, and evaluation of collaboration. The collaboration model used is a participatory exploratory conceptual model which emphasizes that collaboration actors constructively explore existing possibilities and find solutions to obstacles encountered in tourism development. The analysis method used in this study is a qualitative descriptive method and is analyzed using an Nvivo-based application to carry out the process of mapping supporting variables for the collaboration model used so that the analysis results are unbiased and credible, determining the collaboration model, analyzing obstacles faced in implementing the collaboration model, and drawing conclusions and suggestions. The model that is suitable to be applied is a participatory conceptual model, namely collaboration between all components in the village. So that good synergy will have a positive impact on the development of sustainable tourism in Selumbung Village. Obstacles in realizing Selumbung Village include: studies that are not yet sustainable, business capital/budget, lack of investors, there are still human resources that are not yet competent, development is not yet sustainable, and limited integrated information technology facilities, internet access from all providers is not yet available, and others.